Methods for evaluating peak oxygen uptake and anaerobic threshold in upper body of cross-country skiers - Wisloff, U.; Helgerud, J. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: The aim of the present study was to develop a standard protocol for evaluating peak oxygen uptake and anaerobic threshold during upper body work by cross-country skiers. METHODS: All tests were performed on a specially developed ski ergometer and incorporated the double poling technique. In series I, continuous and discontinuous protocols for measuring VO2peak at different inclinations of the ski ergometer were performed. In series II, a protocol for evaluating anaerobic threshold during upper body work was established. Eleven well trained regional male cross-country skiers participated in the study. All tests in each series were carried out during a period of 14 d. RESULTS: VO2peak did not differ using continuous or discontinuous protocol while working on the ski ergometer. Inclination was found to influence VO2peak, which was reduced at 7 degrees compared with 3 degrees, 5 degrees, and 6 degrees. Th(an) working on the ski ergometer was reached at a power output, VO2, or fc, which gave on average a blood lactate concentration of 1.8 mmol.L-1 higher than those found after the warm-up period during a graded protocol. CONCLUSIONS: Testing only the traditional Th(an) and VO2max while running on a treadmill hides important determinants of endurance in cross-country skiing as shown by that no correlation was found between VO2max and VO2peak in the present study.